1977
DOI: 10.1172/jci108791
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Liver in Glucagon Metabolism

Abstract: A B S T R A C T Total plasma immunoreactive pancreatic glucagon (IRG) was measured in samples taken simultaneously from the proximal portal vein and superior vena cava of 26 healthy rats. The portalperipheral ratio of IRG was 2.80±0.25, the portalperipheral difference (A) 124±15 pg/ml, and percentage extraction 58±+3. Gel filtration of paired portal and peripheral vein samples showed that reduction in the 3,500-dalton IRG component (glucagon) in peripheral samples accounted for almost all the differences, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 21 publications
(29 reference statements)
2
19
0
Order By: Relevance
“…Furthermore, little data are available on the hepatic clearance of glucagon in normal rats (41) and none in VMH-lesioned animals. Our perfusion data are compatible with what may happen in the portal vein in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, little data are available on the hepatic clearance of glucagon in normal rats (41) and none in VMH-lesioned animals. Our perfusion data are compatible with what may happen in the portal vein in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Under transient conditions, 2 min after glucagon injection, the dependence of the increase in glucose 6-phosphate on hormone concentration was studied. With 0.2nmol glucagon/l, which can be regarded as a physiological concentration in the portal vein [20,211, the content of glucose 6-phosphate was doubled; it was more than tripled with 15 nmol/l (Fig. 2).…”
Section: Distribution Of Glucose and Glucose 6-phosphatementioning
confidence: 96%
“…Assuming an extracellular space of 30 ml/l50 g body weight [19] injection of 150 pg, 1.5 pg and 25 ng glucagon (molecular weight 3500) yielded an extracellular hormone concentration of 1.5 pmol/l, 15 nmol/l and 0.2 nmol/l, resp. With the calculation of the latter value a basal glucagon concentration of 0.05 nmol/l was taken into consideration [20,211.…”
Section: Glucagon Treatmentmentioning
confidence: 99%
“…Recent studies have pointed out that plasma glucagon immunoreactivity is heterogeneous (Valverde et al, 1970;Valverde et al, 1974;Weir et al, 1975;Valverde and Villanueva, 1976;Kuku et al, 1976;Jaspan et al, 1977) and has as many as four fractions when determined with antiserum 30K. There is at present little information regarding the immunoreactive nature of Big Plasma Glucagon (BPG) (Valverde et al, 1974) and 2000 mol.…”
Section: Endocrinolmentioning
confidence: 99%
“…Jaspan et al (1977) showed that the liver was the major metabolic site of the 3500 molecular weight glucagon.…”
mentioning
confidence: 99%